Serological muscle loss biomarkers: an overview of current concepts and future possibilities. Issue 1 (21st September 2012) - Nedergaard, Anders; Karsdal, Morten A.; Sun, Shu; Henriksen, Kim
Abstract : Background: The skeletal muscle mass is the largest organ in the healthy body, comprising 30–40 % of the body weight of an adult man. It confers protection from trauma, locomotion, ventilation, and it represents a "sink" in glucose metabolism and a reservoir of amino acids to other tissues such as the brain and blood cells. Naturally, loss of muscle has dire consequences for health as well as functionality. Muscle loss is a natural consequence of especially aging, inactivity, and their associated metabolic dysfunction, but it is strongly accelerated in critical illness such as organ failure, sepsis, or cancer. Whether this muscle loss is considered a primary or secondary condition, it is known that muscle loss is a symptom that predicts morbidity and mortality and one that is known to impact quality of life and independence. Therefore, monitoring of muscle mass is relevant in a number of pathologies as well as in clinical trials as measures of efficacy as well as safety. Methods and results: Existing biomarkers of muscle mass or muscle loss have shown to be either too unreliable or too impractical in relation to the perceived clinical benefit to reach regular clinical research or use. We suggest serological neoepitope biomarkers as a possible technology to address some of these problems. Blood biomarkers of this kind have previously been shown to respond with high sensitivity and shorter time to minimum significant change than available biomarkers of muscle mass. We provide brief reviews of existing muscle mass or function biomarker technologies, muscle protein biology, and existing neoepitope biomarkers and proceed to present tentative recommendations on how to select and detect neoepitope biomarkers. Conclusion: We suggest that serological peptide biomarkers whose tissue and pathology specificity are derived from post‐translational modification of proteins in tissues of interest, presenting so‐called neoepitopes, represents an exciting candidate technology to fill out an empty niche in biomarker technology.